2016
DOI: 10.1111/bjd.14895
|View full text |Cite|
|
Sign up to set email alerts
|

Factors driving the use of dermoscopy in Europe: a pan-European survey

Abstract: Expanding access to dermoscopy equipment, especially in public healthcare facilities and establishing dermoscopy training during dermatology residency would further enhance the substantially high dermoscopy use across European countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
32
0
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 41 publications
6
32
0
9
Order By: Relevance
“…It is thus of vital importance to examine how to further reduce biopsies by dermoscopy also in public hospitals. Our prior finding had revealed that dermatologists working in public facilities were the least likely to use dermoscopy at all, or if they used it, it was less intensively; they were also the most likely to report the lack of dermoscopy equipment as a barrier to use dermoscopy. Therefore, proper training and improved access to dermoscopy equipment, especially digital, may be the main ways to address this issue in public hospitals.…”
Section: Discussionmentioning
confidence: 95%
“…It is thus of vital importance to examine how to further reduce biopsies by dermoscopy also in public hospitals. Our prior finding had revealed that dermatologists working in public facilities were the least likely to use dermoscopy at all, or if they used it, it was less intensively; they were also the most likely to report the lack of dermoscopy equipment as a barrier to use dermoscopy. Therefore, proper training and improved access to dermoscopy equipment, especially digital, may be the main ways to address this issue in public hospitals.…”
Section: Discussionmentioning
confidence: 95%
“…This heterogeneity poses significant limitations in evaluating the results of different studies comparatively, in designing new studies on the basis of pre‐existing evidence and, overall, in expanding and spreading the existing knowledge in dermoscopy of dermatological diseases. Indeed, dermoscopy in general dermatology is still seen with reservation by some colleagues and has not yet acquired a standard role in the daily practice for applications other than skin neoplasms, despite evidence suggesting that it improves diagnostic accuracy …”
mentioning
confidence: 99%
“…In the article by Forsea et al , an author's surname among the members of the Eurodermoscopy Working Group was misspelt as J. Hegy. It should have been J. Hegyi.…”
mentioning
confidence: 99%